Analysis of Leadership Style at UPT Puskesmas Kutalimbaru, Deli Serdang Regency - Putri, Dwi Melisa; Salwa, Fadillah; Khumaira, Luthfiah; Vanda, Medina Elly; Wulandari, Nadiah; Sagala, Shinny Syafitri; Putri, Dea Hamiche; Agustina, Dewi (PROMOTOR, 2024)
This study aims to analyze the leadership style in UPT Puskesmas Kutalimbaru, Deli Serdang Regency. The research method used was an in- depth interview with the Head of UPT Puskesmas Kutalimbaru as the main informant. The results showed that Kutalimbaru Health Center implements collaborative decision making, where employees are involved in the process. Although the final decision remains in the hands of the Head of the Puskesmas, suggestions and opinions from employees are considered. Factors such as distance, time, and human resources are the main considerations in running the program. Good cooperation with health workers and community leaders is emphasized to overcome obstacles. This study provides an in-depth understanding of the leadership style at Kutalimbaru Health Center, which is expected to improve the effectiveness of public health services.